Structures and phase transitions in neat 4, 4′-di-tert-butyl-2, 2′-bipyridyl and in its molecular complexes with either bromanilic or iodanilic acid. Issue 45 (8th November 2017) - Rok, M.; Szklarz, P.; Moskwa, M.; Kijewska, M.; Baran, J.; Bator, G.; Medycki, W.; Zamponi, M.
Abstract : Using the DSC method, structural phase transitions (PTs) have been found at 165 and 219 K for 4, 4′-di- tert -butyl-2, 2′-bipyridyl (dtBBP ), whereas for its complex with iodanilic acid (dtBBP·IA ) PT is found at 331 K. Abstract : Using the DSC method, structural phase transitions have been found at 165 and 219 K for 4, 4′-di- tert -butyl-2, 2′-bipyridyl (dtBBP ), whereas for its complex with iodanilic acid (dtBBP·IA ), its phase transition is at 331 K. For the other molecular complex described (with bromanilic acid, dtBBP·BRA ), no phase transitions have been observed between the liquid nitrogen temperature and the temperature of crystal decomposition. The crystal structures of the neatdtBBP have been determined at 130, 190 and 250 K, whereas for its molecular complex with bromanilic acid (BRA) is determined at 150 K and for its complex with iodanilic acid (IA) determined at 293 and 345 K. The crystal structure of neatdtBBP is characterized by layers of molecules, which are grouped by their t -butyls. The structures ofdtBBP·BRA anddtBBP·IA are analogous to one another and consist of infinite chains of alternating acid and base molecules linked by hydrogen bonds. On the basis of the structural, dielectric and spectroscopic results (infrared and Raman), the mechanisms of the phase transitions have been proposed fordtBBP anddtBBP·IA . The 1 H NMR spin–lattice relaxation times for all compounds under study, as well as the second moment for the neat dtBBP in a wide temperature, have been measured. The anomalies in the temperature dependent infrared spectra together with the NMR results support the supposition that fordtBBP the dynamics of tert -butyl groups is responsible for the mechanism of the phase transitions found. The dynamics of the molecules in the crystals presented is related to the rotation both of the methyl and tert -butyl groups.